2017
DOI: 10.1016/j.jiac.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide surveillance of bacterial respiratory pathogens conducted by the surveillance committee of Japanese Society of Chemotherapy, the Japanese Association for Infectious Diseases, and the Japanese Society for Clinical Microbiology in 2012: General view of the pathogens' antibacterial susceptibility

Abstract: a b s t r a c tThe nationwide surveillance on antimicrobial susceptibility of bacterial respiratory pathogens from patients in Japan, was conducted by Japanese Society of Chemotherapy, Japanese Association for Infectious Diseases and Japanese Society for Clinical Microbiology in 2010.The isolates were collected from clinical specimens obtained from well-diagnosed adult patients with respiratory tract infections during the period from January and April 2010 by three societies. Antimicrobial susceptibility testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…S. pneumoniae is generally susceptible to penicillins; however, K. pneumoniae is frequently resistant to penicillins because it produces a penicillin-specific β-lactamase (34), which may result in treatment failure of the initial antibiotics. Results of the antibacterial susceptibility of isolated Klebsiella species in our patients were similar to those reported throughout Japan (35).…”
Section: Discussionmentioning
confidence: 99%
“…S. pneumoniae is generally susceptible to penicillins; however, K. pneumoniae is frequently resistant to penicillins because it produces a penicillin-specific β-lactamase (34), which may result in treatment failure of the initial antibiotics. Results of the antibacterial susceptibility of isolated Klebsiella species in our patients were similar to those reported throughout Japan (35).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the proportion of BLNAR strains in the HI of respiratory tract was significantly higher than that of the urinary tract [24]. Notably, the majority of the ampicillin-resistant HI strains in Japan were BLNAR [9, 25]. Our research group has previously compared the antibiotic resistance of vaginal isolates to respiratory isolates in children and found that respiratory isolates were resistant to ampicillin, cefuroxime, clarithromycin, and trimethoprim-sulfamethoxazole at significantly higher rates than were vaginal isolates [13]; the results of this previous study were consistent with the present multicenter study.…”
Section: Discussionmentioning
confidence: 99%
“…The last surveillance study (including cefditoren among the antimicrobials tested) found in the literature, a surveillance study in Japan, showed MIC 50 /MIC 90 values of cefditoren of 0.125/0.5 mg/l. [ 50 ]…”
Section: Pharmacoepidemiology Of Resistances In Human-adapted Respiramentioning
confidence: 99%
“…In Spain BLNAR isolates increased in parallel with decreases in β-lactamase producing-isolates [ 60 ], and the last published study determining susceptibility of invasive H. influenzae isolates showed up to 19% gBLNAR isolates compared with 16.9% isolates resistant due to β-lactamase production [ 61 ]. Similarly, a recent report from Japan showed the lower percentage of ampicillin-resistant strains due to β-lactamase production (5.6%) than to BLNAR (37.2%) among NTHi respiratory isolates [ 50 ]. In Sweden, the increase in β-lactam resistance among invasive H. influenzae isolates has also been attributed to the significant increase in BLNAR isolates [ 62 ].…”
Section: Pharmacoepidemiology Of Resistances In Human-adapted Respiramentioning
confidence: 99%